Enhancing yield and quality: research and practice of agro-forest waste for Lentinus edodes (shiitake mushroom) cultivation - Xu, Hongyan; Han, Guocai; Li, Yanyan; Meng, Qing; Zhang, Yang; Wang, Yayi; Li, Songling (Frontiers in Nutrition, 2025)
IntroductionCurrent research primarily focuses on exploring and developing innovative substrates for cultivating Lentinus edodes, aiming to address substrate shortages and the continuous rise in production costs.MethodsThis study uses Quercus (oak) sawdust (OS) as a control to evaluate the potential of Korshinsk peashrub (KP), Hippophae rhamnoides (seabuckthorn) pruning (HRP), and Lycium barbarum (goji) pruning (LBP) in the cultivation of L. edodes by measuring parameters such as mycelium growth, yield, protein, fat, fiber, amino acids, soluble sugars, and organic acids. Furthermore, principal component analysis and official script function analysis were used to investigate the influence of the matrix formula ratio on the nutritional values of shiitake mushrooms.ResultsResults showed that the average duration to complete stages 2 and 3 of mycelial growth on 10% KP substrates significantly decreased compared to the OS group by 11.0 and 10.7 days, respectively. The weight of mushrooms produced from all agro-forest waste substrates was significantly lower than that of the control group, decreasing by 18.96 to 53.88%. The average mushroom weight for KP groups ranged from 235.37 g/kg to 252.27 g/kg, which was statistically higher than that of the LBP treatments, which ranged from 143.56 g/kg to 165.96 g/kg. However, the protein content in the 10% LBP and 10% HRP groups was significantly higher than that of the control, with increases of 4.69 and 12.89%, respectively, and fiber content also improved, increasing by 3.98 to 12.59%. Furthermore, the content of sweet-tasting amino acids in the 10% KP and 20% KP groups significantly increased compared to the OS group (by 34.86 and 144.92%, respectively). The 30% LBP and 10% KP-10% LBP-10% HRP groups exhibited higher glucose values compared to the OS (increased by 118.71 and 72.26%, respectively). Interestingly, the addition of LBP and KP to the substrates promoted the synthesis of acetic acid in shiitake mushrooms, while this organic acid was not detected in the OS. In summary, shiitake mushrooms cultured in 20% KP, 10% LBP, or 10% KP-10% LBP-10% HRP demonstrated significantly better overall performance.DiscussionThis approach not only reduces operational costs by at least 1,680 RMB but also contributes to environmental sustainability by diverting 2,400 kg of agro-forest waste from landfills. Consequently, the utilization of agroforestry waste serves as an effective strategy not only for environmental protection and cost reduction during mushroom production but also for enhancing the nutritional value of shiitake mushrooms. This, in turn, helps combat malnutrition and contributes to national food security.